Oral Health Therapy Graduates’ Preparedness for Practice in Aotearoa New Zealand - Smith, Jacqui (Auckland University of Technology, 2026)
Background/Introduction Oral health therapists (OHTs) deliver oral health care to diverse communities across Aotearoa New Zealand (NZ). However, there is limited research examining OHTs’ preparedness for practice in NZ and internationally. Studies on dentists’ and other oral health professionals’ preparedness for practice, in NZ and internationally, suggest an adequate level of preparedness with notable gaps in complex clinical and cognitive tasks (Ali et al., 2017; Almahdi et al., 2023; Altan et al., 2024; Gaballah et al., 2025; Javed et al., 2024; Javed et al., 2023; Mat Yudin et al., 2020; Nalawade et al., 2024). The aim of this research was to explore the oral health therapy graduates’ preparedness for practice and to explore factors that influence preparedness. Methods A mixed-methods approach, using an anonymous online survey, was distributed to OHT graduates from NZ universities who graduated between 2020 and 2023. The survey included demographics, a modified version of the Dental Undergraduates’ Preparedness Assessment Scale (DU-PAS), Likert-type items, and open-ended items. Results Seventy-nine eligible responses were received (response rate 24.5%). Most participants were female (88%), and 52% were aged 24–28 years. The mean total DU-PAS score was 73.1 ± 13.4, with higher scores in Part B (behavioural/cognitive domain; 39.3 ± 7.8) than Part A (clinical domain; 33.8 ± 8.0). Participants felt mostly confident in core clinical and behavioural domains but reported challenges in areas with limited undergraduate exposure. Key factors that influenced preparedness included clinical experience, COVID-19, mentorship, personal attributes and experiences, curriculum and teaching, real-world preparation, and transition. Conclusion Overall graduates felt mostly clinically and cognitively prepared for practice, with confidence levels comparable to international counterparts. However, gaps were noted in advanced clinical knowledge, treatment planning, and some behavioural and cognitive domains. Multiple factors, both intrinsic and extrinsic, influenced OHTs’ preparedness for practice, highlighting its complex nature. Key recommendations to increase graduates’ preparedness include increasing clinical placement and simulation hours, aligning curriculum with real-world practice conditions for universities, introducing scaffolded transitional support structures for all new graduates, and conducting further research to explore the nuances associated with OHTs’ preparedness for practice.